Induction of cytotoxicity by Bruguiera gymnorrhiza in human breast carcinoma (MCF-7) cell line via activation of the intrinsic pathway - Gul-; Nurul Huda Rahman; Vigneswari Sevakumaran; Aziz Ahmad; Habsah Mohamad; Muhammad Naveed Zafar; Yeong Yik Sung; Tengku Sifzizul Tengku Muhammad (Wolters Kluwer Medknow Publications, 2020)
Breast cancer is among the frequently occurring cancer worldwide. The foremost underline aim of this study was to determine the growth inhibitory effect along with mechanistic study of a Bruguiera gymnorrhiza extract on MCF-7. The cytotoxicity activity was determined by using the MTS assay. Butanol extract exhibited the maximum cytotoxicity activity against the MCF-7 cells with IC50of 3.39 μg/mL, followed by diethyl ether and methanol extract (IC50at 16.22 μg/mL and 37.15 μg/mL, respectively) at 72 h. The DeadEndTM Colorimetric Apoptosis Detection System confirmed the induction of apoptosis (via DNA fragmentation) in MCF-7 cells. Both butanol and diethyl ether extracts of B. gymnorrhiza significantly increase the caspase-3 level. However, the diethyl ether extract induced higher caspase-9 levels compared to caspase-8, suggesting that the intrinsic pathway was the major route in the process of apoptosis. Thin-layer chromatography profiling demonstrated the presence of phenolic, terpene, and alkaloid compounds in crude methanol, diethyl ether, and butanol extracts. The phytochemicals present in the extracts of B. gymnorrhiza might have the potential to be a future therapeutic agent against breast cancer.